2023
DOI: 10.1186/s12870-023-04168-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering early transcriptional regulation during adventitious root formation in Medicago sativa

Abstract: Background Alfalfa (Medicago sativa L.) as an important legume plant can quickly produce adventitious roots (ARs) to form new plants by cutting. But the regulatory mechanism of AR formation in alfalfa remains unclear. Results To better understand the rooting process of alfalfa cuttings, plant materials from four stages, including initial separation stage (C stage), induction stage (Y stage), AR primordium formation stage (P stage) and AR maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…SAUR15 can promote adventitious root development of Arabidopsis via auxin accumulation by activating auxin biosynthesis genes ( Yin et al., 2020 ). Previous research also found that in the induction phase of AR production, SAUR was mainly up-regulated, but down-regulated in the root primordium formation stage ( Ai et al., 2023 ), and we screened out a SAUR gene ( auxin-responsive protein SAUR32-like , LOC114266460 ) in CS0 vs. TS0. SAUR71 ( LOC114290786 ) also found at S2 stage may indicate the existence of root primordium induction process triggered by AMF.…”
Section: Discussionmentioning
confidence: 99%
“…SAUR15 can promote adventitious root development of Arabidopsis via auxin accumulation by activating auxin biosynthesis genes ( Yin et al., 2020 ). Previous research also found that in the induction phase of AR production, SAUR was mainly up-regulated, but down-regulated in the root primordium formation stage ( Ai et al., 2023 ), and we screened out a SAUR gene ( auxin-responsive protein SAUR32-like , LOC114266460 ) in CS0 vs. TS0. SAUR71 ( LOC114290786 ) also found at S2 stage may indicate the existence of root primordium induction process triggered by AMF.…”
Section: Discussionmentioning
confidence: 99%
“…The heterologous overexpression of LkWOX4 from Larix kaempferi in 84 K poplar altered the number and length of AR as well as remodeled the transcriptome, and the expressions of phytohormone-signaling genes ( ARF2 , ARF3 , ARF7 , and ARF18 ), rooting-associated transcription factors ( WOX5 , LBD29 , and SCR ), and root development-associated genes ( CYCD3 , GRF1 , and TAA1 ) were modulated [ 32 ]. In addition, transcription factors, such as MYB , NAC , MADS-box , WRKY , bHLH , bZIP , and GRAS families, have also been found to mediate AR formation [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The phenylpropanoid metabolism plays a significant role in plant development and stress tolerance, and it is regulated by various plant hormones, including auxins, ethylene, JA, strigolactones (SL), and gibberellins (GA) [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%